Immune Protective Evaluation Elicited by DNA Vaccination With Neospora caninum Dense Granules Proteins in Mice - Yu, Guili; Liang, Wei; Yang, Qiankun; Wang, Jinxin; Wang, Yu; Zhang, Tianmeng; Zhang, Xiao; Fan, Hui; Zhao, Panpan; Cao, Lili; Dong, Jingquan (Frontiers in Veterinary Science, 2021)
Nesopora caninum, an obligate intracellular protozoan, is the major cause for neosporosis and brings serious economic losses to cattle breeding industries worldwide. After invasion, dense granules proteins are abundantly secreted and being important components of parasitophorous vacuole and intravacuolar network where N. caninum survives and replicates. The aim of the present study was to evaluate the protective immunity induced by DNA vaccines with genes encoding dense granules proteins 1 (GRA1), GRA4, GRA9, GRA14, GRA17, GRA23 against N. caninum tachyzoites in BALB/C mice. Eukaryotic expressing plasmids of pcNcGRAs were constructed and the mice were intramuscularly immunized with pcNcGRAs followed by challenging infection with lethal doses of N. caninum. Immune responses were evaluated through monitoring the levels of serum antibodies, measurement of lymphocyte proliferation, and secretion of cytokines. Immune protection assays were carried out through monitoring survival time, body weight and parasites burden in the brains. Results showed that all the pcNcGRAs DNA vaccines could trigger remarkably specific humoral and cellular responses, with higher levels of IgG and IgG2a antibodies as well as obviously increased secretion of Th1-type IFN-γ cytokines. The immune protective efficacy revealed that pcNcGRA4, pcNcGRA14, and pcNcGRA17 DNA vaccines could individually increase the survival rate to 50%, 37.5%, 25% in comparison with 0% in the control group, prolong the survival time more than 20.88±11.12, 18.88±10.83, 16.63±10.66 days compared to the control group of 4±1.31 days, decrease parasites burden in the brains to 297.63±83.77, 471.5±110.74, 592.13±102.2 parasites/100 ng comparing with 1221.36±269.59 parasites/100 ng in the control group. These findings indicated that NcGRA4, NcGRA14, and NcGRA17 are potential vaccine candidates, NcGRA4 displayed better performance in immune protective efficacy, and could be further combined with other advantageous antigens applied to the development of safe and effective DNA vaccines against N. caninum.